Pretreatment of palm oil mill effluent (POME) for Spirulina cultivation - Ilham Basra; Lusiana Silalahi; Wahyu Diski Pratama; Falvocha Alifsmara Joelyna (BIORE Scientia Academy, 2023)
Palm Oil Mill Effluent (POME) is liquid waste produced from palm oil processing. The quantity of POME in Indonesia has increased from year by year. POME is not a toxic material, but it will be very dangerous if it is thrown directly without pre-processing, because it will harm the aquatic ecosystem due to its high content of COD (Chemical Oxygen Demand) and BOD (Biological Oxygen Demand). POME has also a high content of nitrogen (N) and phosphor (P), which make POME can be used as medium for microalgae growth. Therefore, this research is aimed to study pretreatment and to utilize its nutrient content (N, P) for medium of spirulina growth. Pretreatment of POME research was conducted by using two stage of cultivation (Chlamydomonas and Chlorella) and dilution factor (0-4x). The result of this pretreatment was then used for Spirulina growth. Spirulina cultivation was conducted by nutrient addition and without nutrient addition. This research showed that the best performing variation of dilution rate to cultivate Spirulina is 4x dilution. It showed that 4x dilution could reduce COD content until 128.33 mg/L. Besides that, in 4x dilution, microalgae as Chlamydomonas, Chlorella, and Spirulina had the highest growth rate as compared to 2x dilution and without dilution. The best wild algae for pretreatment of POME is Chlorella. Because by using wild algae Chlorella, COD content could be reduced until 128.33 mg/L and achieve the lowest COD content compared with Chlamydomonas. For microalgae growth, addition of nutrient is better than without nutrient, because nutrient could enhance Spirulina photosynthesis.